Application Of Stad Learning Method By Using Picture Methods In Interactive Learning Can Improve Results Of Student Science - Jasni Elti (Fakultas Sastra Universitas Ekasakti, 2018)
To learn a lesson well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to